The National SOM Survey 2004 - SOM Institute, University of Gothenburg (University of Gothenburg, 2006)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the nineteenth survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health.

One third of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background. The questionnaire on politics include twelve different subject fields: news; politics and society; the surrounding world; media and possession of technical equipment; journalism and society; society, public service and democracy; animals and nature; knowledge and society; environment and energy; activities and interests; work life; and background questions. The media questionnaire is divided into eleven subject fields: news and papers; politics and society; radio and television; possession of technical equipment, internet and other media; periodicals, books and libraries; advertisment and media; journalism and society; activities, interests, and values; work life; background questions; and 'yesterday activities'.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den nittonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2004 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. Frågeformulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. Cirka en tredjedel av frågorna är gemensamma för de båda frågeformulären och kan därmed analyseras med dubbla urvalsstorleken som grund.

Politikformuläret innehåller tolv olika frågeområden: nyheter; politik och samhälle; omvärldsfrågor; medier och teknikinnehav; journalistik och samhälle; samhälle, service och demokrati; djur och natur; kunskap och samhälle; miljö och energi; aktiviteter och intressen; arbetsliv; samt bakgrundsfrågor. Medieformuläret tar upp elva frågeområden: nyheter och tidningar; politik och samhälle; radio och TV; teknikinnehav, internet och andra medier; tidskrifter, böcker och bibliotek; reklam och medier; journalistik och samhälle; aktiviteter, intressen och värderingar; arbetsliv; bakgrundsfrågor; samt gårdagsaktiviteter.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2004
Riks-SOM 2004
Keywords: mass media; massmedia; population migration; migration; energy; energi; nuclear energy; kärnkraft; political participation; politiskt deltagande; internal politics; inrikespolitik; visits to recreational facilities; fritidsanläggningsbesök; citizen participation; medborgardeltagande; leisure time activities; fritidsaktiviteter; mass media use; mediaanvändning; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap